Essays on horse subjects - Grenside, F. C. (Frederick Clement), 1855-1949 (Salt Lake City, UT : Project Gutenberg, 2025)
"Essays on Horse Subjects" by F. C. Grenside is a collection of essays centered on various aspects of horse management and care, written in the early 20th century. The essays draw upon Grenside's extensive experience as a practical horseman and veterinarian, addressing topics often overlooked in equine literature. The text aims to illuminate the complex interplay between horse anatomy, care, and performance, offering insights valuable to both horse owners and trainers. The opening of the collection lays out the author's intent and establishes the purpose of the essays. Grenside explains that the essays were born from his contributions to equine publications and aim to fill a gap in horse-related literature. He emphasizes the importance of understanding concepts like "quality" in horses$1 (Bwhat it means, its attributes, and its implications for breeding and performance. He passionately discusses how various physical traits can affect a horse's health and performance, setting the stage for the essays that will follow, which promise to offer practical advice based on both scientific understanding and hands-on experience. (This is an automatically generated summary.)s
Quality in horses -- Hereditary unsoundness in horses -- Hitching in horses -- Horseshoeing and horses' hoofs -- Correct action in horses -- Forging, over-reaching and clicking -- Interfering, striking, cutting or brushing in horses -- The horse's mouth -- Turning horses out -- Bitting, shoeing and conditioning for action -- Exercise for horses -- The horse's coat in spring, summer, autumn and winter -- The causes of digestive disorders -- The use of burrs on horse's bits.
Release date is 2025-03-20
Carol Brown, Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Horses -- Training; Horses